2020
DOI: 10.1111/dth.13288
|View full text |Cite
|
Sign up to set email alerts
|

Cryopeeling versus trichloroacetic acid peeling in the treatment of solar lentigines: Effect on epidermal Langerhans cells

Abstract: Trichloroacetic acid (TCA) peeling may be effective in solar lentigines, but with concerns regarding potential tumorigenesis. Cryopeeling would be better with improving the whole sun‐damaged skin. We aimed to compare the efficacy and safety of cryopeeling and TCA 35% peeling for treatment of solar lentigines and assess their influence on the number of epidermal Langerhans cells (LC). Twenty‐five patients were treated with TCA 35% and cryopeeling on the right and left hands, respectively. Two sessions were done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…21 In the same study, cryopeeling yielded faster and better improvement of SLs compared to TCA 35%. 21 Similarly, Raziee et al 22 reported better results with cryotherapy compared to TCA 33%, while Golforoushan et al 23 demonstrated comparable efficacy of TCA and cryotherapy. On the contrary, Seirafi et al 24 concluded that long-pulse pulsed dye laser with compression was superior to cryotherapy in the treatment of SLs in darker skin types.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…21 In the same study, cryopeeling yielded faster and better improvement of SLs compared to TCA 35%. 21 Similarly, Raziee et al 22 reported better results with cryotherapy compared to TCA 33%, while Golforoushan et al 23 demonstrated comparable efficacy of TCA and cryotherapy. On the contrary, Seirafi et al 24 concluded that long-pulse pulsed dye laser with compression was superior to cryotherapy in the treatment of SLs in darker skin types.…”
Section: Discussionmentioning
confidence: 82%
“…Frequent TCA peeling has been shown to result in a reduced number of epidermal Langerhans cells 20 . In fact, in comparison with cryopeeling, TCA led to a significantly lower number of these cells in a recent study 21 . In the same study, cryopeeling yielded faster and better improvement of SLs compared to TCA 35% 21 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…After title/abstract screening of 4,162 articles and full-text review of 147 articles, 48 articles were included in our review (Figure 1). 2,10–56 Studies were published between 1992 and 2021 and conducted in Asia (50%, n = 24/48), Europe (27%, n = 13/48), North America (19%, n = 9/48), and South America and Africa (2%, n = 1/48 each). Treatment modality categories included laser in 34 studies, cryotherapy in 7 studies, chemical peels and combination treatments in 6 studies each, and topical retinoids and other treatments in 2 studies each.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed a strong reversal of irradiation damage with an increase in CD1positive LCs ( Xu et al, 2018 ). Abd Elazim et al (2020 ) carried out a research on cryopeeling in the treatment of solar freckles, in comparison with peeling with trichloroacetic acid (TCA). CD1a positive LCs were found only in cryopeeling treatment.…”
Section: Cd1amentioning
confidence: 99%